1999
DOI: 10.1152/ajpheart.1999.276.5.h1724
|View full text |Cite
|
Sign up to set email alerts
|

L-type Ca2+current in guinea pig ventricular myocytes treated with modulators of tyrosine phosphorylation

Abstract: Guinea pig ventricular myocytes in whole cell configuration were treated with tyrosine kinase (TK) inhibitors [genistein (Gst), tyrphostin A23 (T23), and tyrphostin A25 (T25)] and with inactive analogs [daidzein, genistin, and tyrphostin A1 (T1)] to measure effects on L-type Ca2+ current ( I Ca,L). Gst inhibited I Ca,L(IC50 = 47 μM) without affecting its time course or shifting the I Ca,L-voltage relationship. At the highest concentration of isoflavone tested (200 μM), I Ca,L was inhibited by 66 ± 7% (Gst), 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 31 publications
4
40
2
Order By: Relevance
“…Orthovanadate, which is an inhibitor of protein phosphatases, increases basal tyrosine phosphorylation and is used to antagonize the effects of PTK inhibitor. For example, orthovanadate has been shown to antagonize the inhibitory effect of genistein on L-type Ca 2ϩ currents and delayedrectifier K ϩ currents in guinea pig ventricular myocytes (26,29). In the present study, pretreatment with orthovanadate had no effect on the inhibitory action of genistein on Kv4.3.…”
Section: Discussioncontrasting
confidence: 55%
“…Orthovanadate, which is an inhibitor of protein phosphatases, increases basal tyrosine phosphorylation and is used to antagonize the effects of PTK inhibitor. For example, orthovanadate has been shown to antagonize the inhibitory effect of genistein on L-type Ca 2ϩ currents and delayedrectifier K ϩ currents in guinea pig ventricular myocytes (26,29). In the present study, pretreatment with orthovanadate had no effect on the inhibitory action of genistein on Kv4.3.…”
Section: Discussioncontrasting
confidence: 55%
“…Under these conditions, 200-ms depolarizations to 0 mV elicited inward I Ca,L that rapidly reached a peak and then inactivated. As previously reported (Ogura et al, 1999), I Ca,L was reversibly inhibited by 100 mM genistein and 100 mM A23 (Figure 1a). These drugs also had reversible effects on holding current at -40 mV (I h ) and end-of-pulse current (I 200 ) at 0 mV ( Figure 1a).…”
Section: Resultssupporting
confidence: 89%
“…In an earlier study on the action of TK inhibitors on L-type Ca 2 þ current (I Ca,L ) in guinea-pig ventricular myocytes (Ogura et al, 1999), we observed that both genistein and the structurally and mechanistically different A23 (Levitzki & Gazit, 1995) caused development of outward current at 0 mV. The current appeared to be CFTR Cl À current (I Cl(CFTR) ), and was not further investigated.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies have demonstrated that the inhibition of tyrosine phosphatase activity by vanadate derivatives has little or no effect on the basal L-type Ca 2 þ current in cardiac myocytes (Wang & Lipsius, 1998;Ogura et al, 1999;Sims et al, 2000;Belevych et al, 2001). On the other hand, inhibition of tyrosine phosphatase activity by PAO, an arsenicbased compound, has been reported to regulate the basal L-type Ca 2 þ channel activity in vascular smooth muscle cells and neurons (Pafford et al, 1995;Wijetunge et al, 1998).…”
Section: Pao Transiently Stimulates the Basal L-type Ca 2 þ Channel Amentioning
confidence: 99%